JULIA S jihad : Tales of the politically, sexually and religiously incorrect: living in the chaos of the biggest muslim democracy / Julia Suryakusuma; Editor, Tim Lindsey dan Julia Suryakusuma - JULIA Suryakusuma; TIM Lindsey (Komunitas Bambu, 2013)
xxxviii, 526 hlm. : Ilus. ; 21 cm.